Evaluating the impact of early childhood education on child development in Lao PDR. Issue 1 (2nd January 2023) - Kamiya, Yusuke; Nomura, Marika
ABSTRACT: Early childhood education (ECE) is important to provide the necessary support for children's healthy development during the preschool period. We evaluated whether ECE positively impacted early childhood development in Lao PDR. We pooled two rounds of nationally representative cross-sectional household surveys — Lao Social Indicator Surveys 2011/2012 and 2017. The study sample included 9316 children 3–4 years old. Multivariate logistic regression and propensity score-matching analysis were performed to estimate the impact of preschool attendance on children's development status. The results showed that preschool attendance positively impacted children's literacy-numeracy, learning ability, physical growth, and social-emotional development. We confirmed that home stimulation by caregivers also positively impacted children's literacy-numeracy and learning abilities. Since there are large socioeconomic and geographical disparities among Laotian children attending preschool, further efforts should be made to promote equitable and inclusive access to ECE in Lao PDR.